2020
DOI: 10.1016/j.arth.2019.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Patient Outcomes Following Total Joint Replacement Surgery: A Comparison of Hospitals and Ambulatory Surgery Centers

Abstract: Background: For several years, many orthopedic surgeons have been performing total joint replacements in hospital outpatient departments (HOPDs) and more recently in ambulatory surgery centers (ASCs). In a recent shift, the Centers for Medicare and Medicaid Services began reimbursing for total knee replacement surgery in HOPDs. Some observers have expressed concerns over patient safety for the Medicare population particularly if Centers for Medicare and Medicaid Services extends the policy to include total hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 23 publications
4
56
0
Order By: Relevance
“…These results align with a previous study that found lower costs of combined surgical and postsurgical care up to 90 days for ASCs compared with inpatient venues for TKA (13%) and THA (15%). 8 Interestingly, this previous study also found that surgical and postsurgical costs of TKA and THA were higher in ASCs compared with HOPDs (~5% for both procedures). 8 Taken together, the findings from the current retrospective analysis of > 126,000 patients support previous reports among smaller samples indicating that shifting more procedures to HOPDs or ASCs from inpatient settings can reduce medical costs.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…These results align with a previous study that found lower costs of combined surgical and postsurgical care up to 90 days for ASCs compared with inpatient venues for TKA (13%) and THA (15%). 8 Interestingly, this previous study also found that surgical and postsurgical costs of TKA and THA were higher in ASCs compared with HOPDs (~5% for both procedures). 8 Taken together, the findings from the current retrospective analysis of > 126,000 patients support previous reports among smaller samples indicating that shifting more procedures to HOPDs or ASCs from inpatient settings can reduce medical costs.…”
Section: Discussionmentioning
confidence: 80%
“…8 Interestingly, this previous study also found that surgical and postsurgical costs of TKA and THA were higher in ASCs compared with HOPDs (~5% for both procedures). 8 Taken together, the findings from the current retrospective analysis of > 126,000 patients support previous reports among smaller samples indicating that shifting more procedures to HOPDs or ASCs from inpatient settings can reduce medical costs. Future research using large claims databases or other sizable real-world sources can confirm whether these trends will continue.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Ambulatory arthroplasty has been a growing trend in the USA for several years. Advocates have emphasized the safety of outpatient procedures and the avoidance of inpatients risks [4]. In the era of COVID-19, same-day or short-stay surgery is especially appealing.…”
Section: The Post-operative Hospital Staymentioning
confidence: 99%
“…SDD arthroplasty can be performed at dedicated Ambulatory Surgical Centres (ASC), hospital outpatient surgery departments (HOSD) and at hospital inpatient wards. The safety of DCA on selected patient population is well documented in all these settings [14,16,17]. Recent publications comparing the inpatient versus outpatient settings concluded that the latter is more time e cient and patients are more likely to achieve discharge criteria on the day of surgery [14,18].…”
Section: Introductionmentioning
confidence: 99%